TANTANGAN GURU PENDIDIKAN AGAMA ISLAM DALAM KEMAJUAN TEKNOLOGI SERTA PENERAPANNYA PADA PROSES PEMBELAJARAN - Damayanti, Rima; Kalsum, Umi; Safitri, Triani; Cahyadi, Ani (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This article explores the challenges and opportunities faced by Islamic Religious Education (PAI) teachers in integrating technology in the era of the Industrial Revolution 4.0. The study employs a library research method, involving data collection from books and scientific articles related to the topic. The focus of the research is on the development of technology in PAI education, which has two main characteristics: the transfer of knowledge and the transfer of values. Although conventional teaching methods are still dominant, there is an urgent need to utilize modern media such as visual, audio, and the internet to make learning more engaging and effective. The integration of technology requires strategic planning, teacher skill development, and adequate infrastructure. The benefits include ease of access, improved learning quality, and support for independent learning. However, challenges such as low digital literacy and inadequate infrastructure must be addressed. The use of technology can increase student interest and creativity but may also lead to dependency and reduce social interaction. In conclusion, wise integration of technology in line with Islamic values can enrich Islamic religious education